2021
DOI: 10.1136/bmjopen-2021-049386
|View full text |Cite
|
Sign up to set email alerts
|

‘We have been in lockdown since he was born’: a mixed methods exploration of the experiences of families caring for children with intellectual disability during the COVID-19 pandemic in the UK

Abstract: ObjectivesThis study aimed to explore the experiences of parents caring for children with intellectual and developmental disabilities (IDD) during the UK national lockdown in spring 2020, resulting from the COVID-19 pandemic.DesignParticipants were identified using opportunity sampling from the IMAGINE-ID national (UK) cohort and completed an online survey followed by a semistructured interview. Interviews were analysed using thematic analysis.SettingInterviews were conducted over the telephone in July 2020 as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 53 publications
6
37
0
1
Order By: Relevance
“…Perceived care burden increased during the pandemic. This is consistent with previous findings (e.g., Budnick et al, 2021 ), and could be explained by an increased care intensity due to the limited access to respite care, residential schools, and day services (Gillespie‐Smith et al, 2021 ; Rogers et al, 2021 ; Wolstencroft et al, 2021 ; Wos et al, 2021 ). Research suggests that the impact of the pandemic on perceived care burden is especially high for relatives who usually rely on these types of professional support (Budnick et al, 2021 ; Courtenay & Perera, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Perceived care burden increased during the pandemic. This is consistent with previous findings (e.g., Budnick et al, 2021 ), and could be explained by an increased care intensity due to the limited access to respite care, residential schools, and day services (Gillespie‐Smith et al, 2021 ; Rogers et al, 2021 ; Wolstencroft et al, 2021 ; Wos et al, 2021 ). Research suggests that the impact of the pandemic on perceived care burden is especially high for relatives who usually rely on these types of professional support (Budnick et al, 2021 ; Courtenay & Perera, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
“…Caring for an individual with intellectual disabilities is associated with several changes in relatives' daily lives (e.g., Yoong & Koritsas, 2012 ). In a study by Wolstencroft et al ( 2021 ), mothers of a child with intellectual and developmental disabilities described social distancing as part of their daily lives, even before the pandemic. As a result of these changes, relatives might have redefined what aspects constitute a good quality of life and what a “good” quality of life entails (Howard et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent quantitative work suggests that the pandemic has had a detrimental impact on the mental health and wellbeing of children with rare neurogenetic conditions in the UK (6,7). For example, in our own work, we demonstrated that children with rare neurogenetic conditions experienced higher levels of internalising and externalising difficulties during the first UK lockdown, and that these difficulties had a significantly greater impact on daily functioning when compared to children in the wider population (6).…”
Section: Introductionmentioning
confidence: 48%
“…We also observed the effect size of these differences were greater than those reported in independent studies prior to the pandemic, highlighting the profound impact of the pandemic on emotional and behavioural difficulties, and daily functioning in children with rare neurogenetic conditions. In another study of families of children with rare neurogenetic conditions during the first UK lockdown, children were reported to experience stress navigating social restrictions and isolation, and worries surrounding COVID-19 infection (7). Taken together, these findings suggest that children with rare neurogenetic conditions' mental health and wellbeing was negatively impacted during the early phases of the pandemic in the UK.…”
Section: Introductionmentioning
confidence: 98%